THE STUDY OF THE SUPERIOR COMODITY IN DEVELOPING HOLTICULTURE BUSINESS IN KECAMATAN WANAYASA KABUPATEN PURWAKARTA - FITRINA (NIM 25406009), VINNA
The developments of agricultural industrialist in Kecamatan Wanayasa involve individuals that include many kinds of professions as well as producer, processor, trader, distributor, importer, exporter etc. They are a component or a subsystem that composes agribusiness systems. These systems will have good function if there is no disturbances in every single subsystem, because of all subsystems must be ready in carrying out the role as professionally. Kecamatan Wanayasa which is part of its area not developed entirely by agriculture, and diversity of commodities develop in farmer level and the differentiations of government policy makes the central government, district government, private company even farmers have different commodity perceptions to be developed in Wanayasa. The Propose of this research is for investigating the superior commodity in Kecamatan Wanayasa that appropriate with agriclimate in developing horticulture business. Based on its functions, the objective of this research is to identify the location of agricultural areas which appropriate with Kecamatan Wanayasa land; to identify superior commodities in horticulture production that appropriate with agriclimat and to identify the development commodity agriculture business especially horticulture that appropriate with farmer level in Kecamatan Wanayasa. To find suitability the potential land for horticulture area in Wanayasa that is carried out by supreme pose physis condition method, then to be overlaid by settlement land existing and shelter area until getting the potensial location for horticulture. In investigating the formulation of superior commodity in farmer level, is processed by seeing the commodity that can be considered as superior in Kecamatan level that appropriate with agriclimate in Kecamatan, the development and displacement of commodity production that develop in Wanayasa. There are16 from 32 commodities which grow and can be considered as superior in Kecamatan level as oranges, mangosteens, avocados, rose apples, papayas, jackfruits, duku, durian, cabbage, frech beans, cucumber, pineapple, petsay, and scallion. The formulation of the superior commodity in farmer level can be investigated by seeing the commodity that grow in farmer level and seeing the farmer perceptions. Cross tabulation to the farmer perceptions are processed based on kind of farmer job as owner farmer or laborer farmer, farmer gender respondent also to the core commodity. Based on the result cross tabulation by seeing kind of farmer's job about farmer understanding in panca usahatani (five orientasi of agricultural business) is majority of 60,9% not onlu male but also female have enough about panca usahatani understanding. It can be seen from the data 54,9% (39 persons) male farmers and 71,8% (28 persons) female farmers that have enough panca usahatani understanding. While in cross tabulation that use the gender of the farmer from 110 respondents is majority of 55,5% (61 persons) not only owner farmer but also laborer farmer are still doubtful to change the commodity. This is can be seen in the data of 27,3% (30 persons) farmer owners and 28,2% (31 persons) is still doubtful to change the commodity.<p.The result of cross tabulation is superior commodity in developing agricultural business at farmer level in Kecamatan Wanayasa, such as mangosteens, durian and French been.